Zygoparity and sex steroid hormone profiles in bluemouth Helicolenus dactylopterus - Sequeira, Vera (2019)
Two hundred and seven individuals (103 females and 104 males) of bluemouth Helicolenus dactylopterus (Scorpaeniformes, Sebastidae), a commercially important deep-water species with an unusual reproductive strategy, from the eastern Atlantic Ocean ranging from 13·9 to 37·5 cm total length (LT ) were analysed from September 2011 to October 2012. The analysis included gonad maturity phases and blood-plasma levels of oestradiol-17β (E2 ), 11-ketotestosterone (11-KT) and 17,20β-dihydroxypregn-4-en-3-one (17,20β-P). Results confirmed the existence of an annual reproductive cycle with asynchrony between females and males and a spawning season from January to May. A pronounced peak in 17,20β-P in October for both sexes was associated with possible mating behaviour and recent copula. Levels of E2 increased preceding the elevation of the gonado-somatic index during ovarian growth and were lower during regression and regeneration. The frequency distribution of oocyte-embryonic stages and variation of hormone levels suggest the existence of daily rhythms. Fertilization was detected between 2000-0000 and 0800-1200 h and spawning took place throughout the day peaking between 2000 and 0000 h. The cyclic pattern of sex steroids and ovarian recruitment provides a new insight into the reproductive strategy of this species.